Polyelectrolyte cellulose gel with PEG/water: Toward fully green lubricating grease. (15th February 2020) - Shetty, Pramod; Mu, Liwen; Shi, Yijun
Graphical abstract: Highlights: Cellulose based fully green gel lubricants were developed. NaCMC gel produces lower friction and wear in comparison to HEC gel. Negative charge and larger molecular weight of NaCMC enhance lubrication property. Abstract: Developing a fully green lubricant is an urgent need due to the growing consciousness of environmental protection and dwindling resources. In this work, fully green gel lubricants were developed out of cellulose derivatives as gelator and mixture of water and poly(ethylene glycol) 200 (PEG 200) as the base fluid. The non-ionic hydroxyethyl cellulose (HEC) and anionic sodium carboxymethyl cellulose (NaCMC) were chosen to understand the effect of ionic and non-ionic gelators on the thermal, rheological and the tribological properties of the gel lubricant. HEC or NaCMC is demonstrated as effective additive to reduce wear, stabilize friction coefficient and enhance the thermal stability of developed lubricants. It is shown that anionic gelator will result in producing lower friction and wear in comparison to non-ionic gelator, which may be attributed to the possible tribo-film formation due to the negative charge in the NaCMC molecules and its larger molecular weight.